Identification of Marbofloxacin-Susceptible Bacterial Uropathogens in Feline Urinary Tract Infection of Different Age Groups - Udasmara, Sekarani Arifah; Retnaningrum, Endah (Biology, Medicine, & Natural Product Chemistry, 2024)
Urinary tract infections (UTI), an adhesion and multiplication of bacterial uropathogens in the urogenital system, are one of the most important indications for antimicrobial use in veterinary medicine and contribute to the development of antimicrobial resistance. Previously, it was revealed that older cats with an average of 9.1 years old are most likely to develop UTI, however a contradicting investigation stated kittens and young adults are more likely to contract UTI. Along with the uprising of amoxicillin- and ampicillin-resistant uropathogens, the study aims to turn towards marbofloxacin reserve and to analyze their potency. Furthermore, the current study aims to enumerate and compare the number of uropathogens between age groups. Enumeration and identification of uropathgoens from urine samples of feline UTI patients were was conducted through the urine culture on EMB, MSA, and BHI medium followed by an IMViC test and inoculation to the Mueller-Hinton agar to observe the zone of inhibition. The investigation revealed that a higher number of younger cats and kittens were reported to have UTI and catheter-induced UTI with a higher number of uropathogens in the population. The uropathogens were further identified as Staphylococcus spp., Enterococcus spp., Enterobacter spp., Escherichia spp., and Klebsiella spp. Additionally, marbofloxacin was found to be effective in eliminating and inhibiting the growth of these uropathogens. In conclusion, younger cats were observed to be more prone to UTI of a diverse range of uropathogens, however, marbofloxacin may aid in the treatment of the cats as it has been proven to be most effective.